Responsible leadership competencies in accounting education - Miller, Taryn (College of Accounting, 2023)
The business world continues to be plagued by incidents of leadership failure, including that of Chartered Accountants (CAs). Responsible Leadership (RL) theory was in part conceived in response to misconduct by business leaders. RL competencies overlap with many competencies expected of CAs, according to international education requirements that inform the CA curriculum. Yet studies continue to show that accounting students are underdeveloped in many competencies affiliated with RL. Furthermore, an institutional strategy for developing RL competencies in accounting students is currently lacking. The purpose of this study is to explore how to incorporate the development of RL competencies into the CA curriculum. The study is grounded within RL, Transformative Learning, curriculum, and curriculum change theories. A qualitative research method was adopted. Interviews were conducted with thirteen South African CA leaders holding a variety of societal and business roles, and eleven CA educators from several South African universities. The study identifies a strategy for RL competency development comprising seven core concepts known as the RESPOND model. Strategic considerations relating to 'what', 'which', 'when', 'where', 'who' and 'how', are addressed in the model. Practical recommendations based on the RESPOND model are provided. The study's findings may assist accounting academics deliberating on adaptations to their curricula to achieve competencies and graduate outcomes synonymous with RL. In addition, the RESPOND model provides a theoretical contribution to the advancement of both accounting education and RL theory by both connecting and expanding knowledge within these research fields.